Implementation of quality management system (QMS) in construction project at Taman Belimbing, Jitra Kedah / Wan Amni Aizah Megat Abdullah - Megat Abdullah, Wan Amni Aizah (Universiti Teknologi MARA UiTM,Perak, 2021)
The research was carried out at No.305, Upper Floor, Jalan Jalai Jaya 1/6, 1, Taman Jalai Jaya, 06200 Kepala Batas, Kedah. TONA GROUP SDN. BHD. has conducted a construction and renovation study. This research was also carried out to learn more about the use of the Quality Management System (QMS) on the construction site. Furthermore, this study was carried out to discover how construction companies use QMS on construction sites. This research can also reveal issues that arise on the construction site before, during, and after the project is completed. The project will last 5 months. It was able to detect some problems during the project within 5 months. The purpose of this research is to determine how to use QMS in each construction company. In addition to understanding the issues with using QMS while running the project. As well as taking appropriate action if such problems arise on the construction site. This research is also carried out in terms of specific procedures or techniques used to identify, select, process, and analyses information about a specific topic. In this project, as a site supervision at TONA GROUP SDN. BHD, researcher need to do Inspections are critical for facilitate the construction and renovation process. Its purpose is to ensure that all planned events go off without a hitch. This research was carried out on the construction site. There are issues in this monitoring, such as material delays, which have caused changes in the planning schedule. The best option is for management to pay attention and plan the schedule more neatly and orderly such as sending materials that have been pre-ordered early. Lastly, do a proper scheduling to make their works easier during construction and renovation works.